Cervical spinal demyelination with ethidium bromide impairs respiratory (phrenic) activity and forelimb motor behavior in rats - Nichols, N.L.; Punzo, A.M.; Duncan, I.D.; Mitchell, G.S.; Johnson, R.A. (Neuroscience, 2013)
► Spinal ethidium bromide injections produced transient dorsolateral demyelination. ► Ventilation did not change with ethidium bromide (EB) demyelination. ► Ipsilateral phrenic nerve amplitude was transiently reduced post-EB. ► Ipsilateral limb function was continually impaired post-EB. ► EB provides a reversible demyelination model to study compensatory motor plasticity. Although respiratory complications are a major cause of morbidity/mortality in many neural injuries or diseases, little is known concerning mechanisms whereby deficient myelin impairs breathing, or how patients compensate for such changes. Here, we tested the hypothesis that respiratory and forelimb motor functions are impaired in a rat model of focal dorsolateral spinal demyelination (ethidium bromide, EB). Ventilation, phrenic nerve activity and horizontal ladder walking were performed 7–14days post-C2 injection of EB or vehicle (SHAM). EB caused dorsolateral demyelination at C2–C3 followed by significant spontaneous remyelination at 14days post-EB. Although ventilation did not differ between groups, ipsilateral integrated phrenic nerve burst amplitude was significantly reduced versus SHAM during chemoreceptor activation at 7days post-EB but recovered by 14days. The ratio of ipsi- to contralateral phrenic nerve amplitude correlated with cross-sectional lesion area. This ratio was significantly reduced 7days post-EB versus SHAM during baseline conditions, and versus SHAM and 14-day groups during chemoreceptor activation. Limb function ipsilateral to EB was impaired 7days post-EB and partially recovered by 14days post-EB. EB provides a reversible model of focal, spinal demyelination, and may be a useful model to study mechanisms of functional impairment and recovery via motor plasticity, or the efficacy of new therapeutic interventions to reduce severity or duration of disease.